A hybrid fluid–kinetic neutral model based on a micro–macro decomposition in the SOLPS‐ITER plasma edge code suite. Issue 5 (25th February 2020) - Horsten, N.; Dekeyser, W.; Blommaert, M.; Samaey, G.; Baelmans, M.
Abstract: We present a hybrid fluid–kinetic model for the hydrogenic atoms in the plasma edge that is implemented in SOLPS‐ITER. A micro–macro decomposition of the kinetic equation leads to a fluid model with a continuity and parallel momentum equation (implemented in B2.5) coupled to a kinetic correction equation (implemented in EIRENE). We assess the hybrid model for a high recycling fixed background plasma. The hybrid approach leads to a reduction of the Central Processing Unit(CPU) time required to obtain the same statistical error as the full kinetic Monte Carlo (MC) simulation with approximate factors of 1.7, 4.9, and 1.9 for the particle, parallel momentum, and electron energy source, respectively. However, there is an increase in CPU time for the ion energy source. By comparing the results with our in‐house plasma edge code, we conclude that the hybrid performance can be improved by adapting some default MC features in EIRENE.